Concevoir des parcours immersifs en français langue seconde pour préparer les étudiants étrangers à la mobilité - Nicolas Guichon; Julien Thiburce; Justine Lascar; Sofiane Doulfaquar (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
With the growing importance of technology-mediated learning, both in the academic world and for the general public, it seems appropriate to assess the possibilities offered by immersive technologies to provide alternative experiences for learning a second language and its culture. The Visiteurs project is based on the design of an immersive course that aims to support the exploration of public space by foreign students. Certain stages of the pilot course design provide a vantage point to examine the contribution of immersive technologies for situated language learning and to generate methods and concepts conducive to fuelling research in instructional design.